Nancy spero : the work - Lyon, Christopher (New York, NY : Prestel Pub., 2010)
Contents: ##Introduction: In and out of history -- An idea of destiny -- Emerging from darkness -- L'artiste revoltee -- The artist and her double -- Woman as protagonist -- La premiere langue -- Theatres de memoires.
boek
Keywords: Spero, Nancy